2020
DOI: 10.1016/j.celrep.2019.12.082
|View full text |Cite|
|
Sign up to set email alerts
|

Integration of eQTL and a Single-Cell Atlas in the Human Eye Identifies Causal Genes for Age-Related Macular Degeneration

Abstract: Highlights d A searchable database of eQTL from macula and peripheral retina and RPE/choroid d Single-cell expression from human retina and RPE with cell subtype resolution d Integrative analysis of bulk and single-cell transcriptomics in the human eye d Co-localization of GWAS and eQTL identified putative causal genes for AMD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
188
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(209 citation statements)
references
References 69 publications
19
188
2
Order By: Relevance
“…Ratnapriya et al (2019) were the first to perform eQTL and TWAS analyses in 406 retinal samples [ 25 ]. This was followed by a study of Orozco et al (2020) that calculated eQTL in 121 retinae and additionally in RPE/choroid samples [ 28 ]. Both studies included, apart from control retinae, additionally AMD patient samples to a variable extend.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ratnapriya et al (2019) were the first to perform eQTL and TWAS analyses in 406 retinal samples [ 25 ]. This was followed by a study of Orozco et al (2020) that calculated eQTL in 121 retinae and additionally in RPE/choroid samples [ 28 ]. Both studies included, apart from control retinae, additionally AMD patient samples to a variable extend.…”
Section: Resultsmentioning
confidence: 99%
“…Orozco et al (2020) [ 28 ] investigated eQTL in a total of 121 samples from retinal and combined RPE and choroid (RPE/choroid) tissue. Further, they distinguished between macular and non-macular tissue and applied a Benjamini and Hochberg FDR threshold of 0.05 [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…By profiling 119,520 single cells, we provided detailed single-cell transcriptomes of adult and aged primate retinae with regional information. The retinal transcriptome at single-cell or single-nuclei level has been reported [3,[9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular differences between the foveal and peripheral retina are important for understanding human visual function. To date, multiple analyses in primates have demonstrated the regionspecific retinal transcriptomes in developing and adult foveal and peripheral retina, suggesting distinct transcriptional regulations in the two regions [3,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the published studies on eQTL and pQTL have not identified pleiotropic regions because they have focused on cis-associations 16,[24][25][26] . Our results indicate that protein expression is regulated at multiple levels and in coordination with other independent proteins, which are likely part of the same signaling pathway.…”
Section: Pleiotropic Locimentioning
confidence: 99%